(untitled) (Ibrahim Medical College Journal, 2009)
Follicular carcinoma of the thyroid usually presents as nodules with rare cases showing metastasis at diagnosis. But occult follicular carcinoma without any thyroid enlargement and presenting as multiple lytic bone lesions is unusual and relatively rare. Here we report a 66-year old Malay man presenting with occipito-parietal swelling for last two years. He had no thyroid enlargement; no thyroid related symptoms and his biochemical thyroid profile was normal. Computerised tomography of skull reported multiple lytic lesions in the occipito-parietal region. FNAC and histopathological examination confirmed the diagnosis of metastatic follicular carcinoma. We present this case because of the rarity of the disease. Ibrahim Med. Coll. J. 2007; 1(2): 25-27 Key Words: Occult follicular carcinoma thyroid, skull metastasis, normal thyroid findings. doi: 10.3329/imcj.v1i2.2906